2003
DOI: 10.1038/sj.gt.3302070
|View full text |Cite
|
Sign up to set email alerts
|

Mouse B7-H3 induces antitumor immunity

Abstract: Members of the B7 family costimulate the proliferation of lymphocytes during the initiation and maintenance of antigen-specific humoral and cell-mediated immune responses. While B7-1 and -2 are restricted to lymphoid tissues, and activate naïve T cells, recently identified members including B7-H2 and -H3 are widely expressed on nonlymphoid tissues, and regulate effector lymphocytes in the periphery. B7-H3 has properties that suggested it may display antitumor activity, including the ability to stimulate Th1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 25 publications
4
109
0
1
Order By: Relevance
“…Lastly, while our data demonstrating a positive regulatory pathway for B7-H3 are consistent with other work [9,12,14], they differ from reports showing negative regulatory functions of mB7-H3 [15,16]. The reasons for this are unclear, though certainly different targeting strategies, assays, and models were employed.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Lastly, while our data demonstrating a positive regulatory pathway for B7-H3 are consistent with other work [9,12,14], they differ from reports showing negative regulatory functions of mB7-H3 [15,16]. The reasons for this are unclear, though certainly different targeting strategies, assays, and models were employed.…”
Section: Discussionsupporting
confidence: 81%
“…mB7-H3.Ig was also found to bind to mitogen-activated but not resting mouse T cells [11], and in line with a proposed stimulatory function of human B7-H3, Sun et al [12] demonstrated that intratumoral injection of an mB7-H3 pcDNA3 expression plasmid led to complete regression of about 50% of the tumors. Subsequent studies of intratumor expression of B7-H3 from the Chen laboratory [14] (where B7-H3 was first described) showed a costimulatory effect of B7-H3 and enhanced tumor immunity in vivo and in vitro in a mouse model.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…B7.1, a member of the B7 family, is located on the surface of antigen-presenting cells and is the natural ligand of CD28 on the T-cell surface (31,32). Through engagement of T-cell receptor with its cognate MHC molecules and B7.1 with CD28, interleukin-2-secreting CD4 + effector cells and CD8 + T cells will be maximally activated (31,32).…”
Section: Introductionmentioning
confidence: 99%